Acceptance, satisfaction and cost of an integrative anthroposophic program for pediatric respiratory diseases in a Swiss teaching hospital: An implementation report. (October 2018) - von Schoen-Angerer, Tido; Vagedes, Jan; Schneider, Romy; Vlach, Livia; Pharisa, Cosette; Kleeb, Simon; Wildhaber, Johannes; Huber, Benedikt M.
Highlights: There are few pediatric inpatient services offering an integrative medicine approach. Anthroposophic treatments were introduced for acute respiratory diseases in the pediatric department of a Swiss teaching hospital. Planning, implementation and evaluation of the 18-month pilot phase are described. Treatment uptake and parent satisfaction were high and costs were outweighed by additional insurance reimbursements. The program is expanded into a center for integrative pediatrics. Abstract: Background: For the pilot phase of an integrative pediatric program, we defined inpatient treatment algorithms for bronchiolitis, asthma and pneumonia, using medications and nursing techniques from anthroposophic medicine (AM). Parents could choose AM treatment as add-on to conventional care. Material and methods: To evaluate the 18-month pilot phase, parents of AM users were asked to complete the Client Satisfaction Questionnaire (CSQ-8) and a questionnaire on the AM treatment. Staff feedback was obtained through an open-ended questionnaire. Economic data for project set-up, medications and insurance reimbursements were collected. Results: A total of 351 children with bronchiolitis, asthma and pneumonia were hospitalized. Of these, 137 children (39%) received AM treatment, with use increasing over time. 52 parents completed the questionnaire. Mean CSQ-8 score was 29.77 (95% CI 29.04–30.5) which is high in literature comparison. 96% of parents were mostly or very satisfied with AM; 96% considered AM as somewhat or very helpful for their child; 94% considered they learnt skills to better care for their child. The staff questionnaire revealed positive points about enlarged care offer, closer contact with the child, more relaxed children and greater role for parents; weak points included insufficient knowledge of AM and additional nursing time needed. Cost for staff training and medications were nearly compensated by AM related insurance reimbursements. Conclusions: Introduction of anthroposophic treatments were well-accepted and led to high parent satisfaction. Additional insurance reimbursements outweighed costs. The program has now been expanded into a center for integrative pediatrics.